2010
DOI: 10.1029/2009jd013600
|View full text |Cite
|
Sign up to set email alerts
|

Deposition velocity of ultrafine particles measured with the Eddy‐Correlation Method over the Nansen Ice Sheet (Antarctica)

Abstract: [1] This work reports an analysis of the concentration, size distribution, and deposition velocity of atmospheric particles over snow and iced surfaces on the Nansen Ice Sheet (Antarctica). Measurements were performed using the eddy-correlation method at a remote site during the XXII Italian expedition of the National Research Program in Antarctica (PNRA) in 2006. The measurement system was based on a condensation particle counter (CPC) able to measure particles down to 9 nm in diameter with a 50% efficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 57 publications
(98 reference statements)
3
25
0
Order By: Relevance
“…Over ice/snow surface, the results suggest that the ZH14 is the most accurate parameterization, and PZ10 is the least accurate. Qualitatively, this finding is consistent with Petroff and Zhang (2010), who reported that their model significantly underestimated the measured deposition velocities over ice/snow surface for the following studies: Ibrahim et al (1983), Duan et al (1988), Nilsson and Rannik (2001), and Contini et al (2010), which were also investigated in the present study. We also note that the Z01 parameterization overestimated the measured V d from the aforementioned studies.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Over ice/snow surface, the results suggest that the ZH14 is the most accurate parameterization, and PZ10 is the least accurate. Qualitatively, this finding is consistent with Petroff and Zhang (2010), who reported that their model significantly underestimated the measured deposition velocities over ice/snow surface for the following studies: Ibrahim et al (1983), Duan et al (1988), Nilsson and Rannik (2001), and Contini et al (2010), which were also investigated in the present study. We also note that the Z01 parameterization overestimated the measured V d from the aforementioned studies.…”
Section: Discussionsupporting
confidence: 80%
“…We note that the studies by Möller and Schumann (1970) and Sehmel et al (1974) were conducted in the wind tunnels, and thus the observed deposition does not necessarily reflect deposition under natural conditions. Particle deposition measurements on ice/snow pack were collected from eight studies: Ibrahim et al (1983), Duan et al (1988), Nilsson and Rannik (2001), Gronlund et al (2002), Contini et al (2010), Held et al (2011a, b), and Donateo and Contini (2014). The parameterizations were fed using reported values of particle properties (diameter and density), meteorological conditions (stability parameter, temperature, wind speed, etc.…”
Section: An Evaluation Of the Dry Deposition Parameterizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, v d is calculated to be 0.15-0.6 cm s −1 globally, which is much larger than the observed v d over ice or snow surfaces (typically 0.02-0.06 cm s −1 , under different atmospheric stabilities) [Duan et al, 1988;Nilsson and Rannik, 2001;Gallagher et al, 2002;Contini et al, 2010]. To better constrain model results with observations, g is increased to 1200 over snow or ice surfaces.…”
Section: Dry Depositionmentioning
confidence: 99%
“…This value was obtained in ten repeated laboratory experiments measuring the complete eddy-covariance flux system response to a concentration step, and the variability observed in these experiments was used to evaluate the uncertainty. This response time proved sufficient to measure concentration fluctuations at frequencies that typically made a substantial contribution to the vertical turbulent fluxes of particles [23,36,37]. However, the high frequency undersampling generates an error on F N that needs to be corrected.…”
Section: Post-processing and Data Selectionmentioning
confidence: 99%